A NAVARASA BASED ANALYSIS OF SONGS FROM THE MOVIE LAGAAN - R. Sailaxmy; Prabakaran V. (ShodhKosh: Journal of Visual and Performing Arts, 2025)
The necessity for sound in a film is undebatable. Music, as sound, can be diegetic and non-diegetic depending on the demands of the story. Music also plays a pivotal role in Indian films as it happens to be an integral part of our culture and audience. It enhances the emotions and adds magic to the overall output of the scene. Despite holding tremendous importance, film music has not been studied adequately. This paper seeks to analyse how music enhances the scenes in films. This analysis will be carried out through the Navarasa Theory from the Natya Shastra. This theory seeks to facilitate our understanding of the emotions that the songs convey to the scene. Every Rasa has got certain Ragas or tunes that convey its appropriate mood. The study shall also draw parallels between these Ragas, their pertaining Rasas and the scenes in the film to understand the correlation between the three. Songs from the movie Lagaan – Once Upon a Time In India, have been selected for the study.